Trabalhos de agulha e prendas domésticas : educação feminina mato-grossense (1889 - 1910) - Mattos, Sandra Jung de (2018)
This study has the objective of discussing and understanding the historic process of the organization of Female Education in the state of Mato Grosso at the beginning of the republican era, 1889 to 1910. It includes itself in the field of History of Education. We promote the mapping of female elementary schools in the state. We used as sources the Constitution of the State of Mato Grosso of 1891, Regulations of Elementary Education in Mato Grosso June 6, 1889, known as the Souza Bandeira Reform, promoted by Antônio Herculano Souza Bandeira, Decree no 10 de November 07, 1891 by State President Manuel José Murtinho, Decree no 68 June 20, 1896 by State President Antônio Correa da Costa, Reports of the Board of Directors about Public Instruction in the State of Mato Grosso from 1889 to 1910, and Messages by the President of the State of Mato Grosso from 1889 to 1910. We established as areas of analysis: Laws and Regulations of Public Instruction, Organization of elementary Instruction and Norms and Regulations for Female Schooling. We sought to answer: How was female education organized? Which and how many female schools were in Mato Grosso during the period from 1889 to 1910? Where were they located? To establish a research base in the History of Female Education and of women, we established a dialogue with authors such as Guacira Lopes Louro (1987, 2014, 2015), Jane Soares de Almeida (1998, 2004, 2014), Michelle Perrot (2005, 2006, 2015). With authors Cynthia Greive Veiga (2007), Otaiza Oliveira Romanelli (1986), Diana Vidal and Luciano Faria Filho (2005) and Dermeval Saviani (2004) we traveled the History of Education in Brazil; Nicanor Palhares Sá and Elizabeth Figueiredo de Sá (2006, 2011), Gervásio Leite (1971), Virgílio Corrêa Filho (2002), Humberto Marcílio (1963) and Rubens de Mendonça (1982), helped us hike the trails of education in Mato Grosso. With Rosa Fátima de Souza (1998) and Paulo Nosella and Ester Buffa (2009), we attended to school institutions. The authors Marc Bloch (2002), José D’Assunção Barros (2010), Lucien Febvre (1989), Peter Burke (1992, 1997), Carlo Ginzburg (1989), and Jacques Le Goff (1990) among others contributed to the understanding and planning of the historic path and investigative methodology. With the primary sources we walked a delicate path that permitted to affirm that even with the changes that the Brazilian Republic proposed for Public Instruction, in Mato Grosso perpetuated for the female education a set of values that attached the formation of women to principles like: submission of woman to parents, husbands and relatives, ascribing to them the mission of managing and caring for the home. The formation was related to the care of the family, education of children and domestic work. It also should be noted that in Mato Grosso there were few female schools compared to male schools. This fact caused the exclusion of women from schooling during the period.